Peningkatan Mutu Molding Injeksi dengan Metode DMAIC Six Sigma - Sihombing, Haeryip; Yaakob, Mohd Yuhazri; Vasu, Suresh (Universitas Mercu Buana, 2011)
The injection moulding is a manufacturing technique for making parts from both thermoplastic and thermosetting plastic materials in production. Actually, the defects occurred on high-pressure process due to the process variations such as temperature, time, pressure, and distance. This paper identifies current quality problems by using Six-Sigma DMAIC methodology. In addition, the classical method is to improve major quality problem in the 30-Ton injection moulding operation carried out for setting parameter. Some aspects regards to the machines are through the main factor analyzed to identify and improve by several activities required, such as the cleaning and scale approachable of its value at the optimum level. The review and analysis of the governing principles on process performance are showing the decreasing of rejection rates by setting a new parameter and optimum range value.